E-Parking Monitoring Using Microcontroller-Based IoT Technology - Muhammad Fachri; Lubis, Imran (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The rapid growth of urban areas has increased the demand for efficient parking systems, particularly in congested public spaces. This study presents the design and implementation of an IoT-based e-parking monitoring system utilizing NodeMCU ESP8266 and infrared (IR) sensors to detect parking slot availability in real time. A web-based interface enables users to monitor and reserve parking slots remotely with secure authentication. Testing results demonstrated that the system provides fast response times (2–21 ms) and accurate real-time updates on the web dashboard. Additional feedback mechanisms, such as buzzer alerts for unauthorized use, further enhance operational efficiency and parking discipline. This research shows that IoT integration significantly improves parking management and offers scalability and potential integration for future urban smart parking systems.